The Effect of Principal Leadership Orientation and Teacher Performance on the Quality of Education at Madrasah Ibtidaiyah (MI) Muhammadiyah - Imtihan, Rofi; Arifiati, Retna Febri; Sumarji (Jurnal Pendidikan Nusantara, 2025)
This study aims to investigate the influence of principal leadership orientation and teacher performance on the quality of education in MI Muhammadiyah Kertonatan Kartasura. The method used in this study was census sampling, which involved 15 teachers as respondents. Data were collected through questionnaires using Likert scale and analyzed by multiple linear regression using SPSS 17.0 software. The results of the analysis show that simultaneously, the principal's leadership orientation and teacher performance have a significant influence on the quality of education, with the contribution of influence reaching 47.0%. Meanwhile, 53.0% of the quality of education is influenced by other variables outside the two factors. The t test and partial correlation coefficient show that teacher performance has a dominant influence on the quality of education at MI Muhammadiyah Kertonatan Kartasura. In conclusion, principal leadership orientation and teacher performance have a significant positive influence on education quality, with teacher performance as the most influential factor. This study emphasizes the importance of developing teacher performance and implementing effective leadership to improve the quality of education in these institutions.